A estetização da doença na ficção de Lúcio Cardoso - Carlos Roberto da Silva (2016)
Considering the interdisciplinary theoretical presuppositions, such as the Anthropology of diseases, the Sociology of health and disease, the Philosophy, the Biomedicine and the Literary Studies, this research aimed at showing that Lúcio Cardoso, in his books 'Maleita', 'Salgueiro' and 'Crônica da casa assassinada', makes use of diseases, such as malaria, small pox, tuberculosis and cancer and their social representations to express metaphorically the modernity that is not fulfilled or is fulfilled through destruction, by corroding a nation project that erupted with the Proclamation of the Republic. Besides, these diseases elaborate the structure of Cardoso's narrative, in which form and contents are considered means of allegories, of which the disease is the guide-line intertwined by social and cultural significations, so as to express the modernized processes that were not fulfilled, because of internal factors of the very history of the foundation of the Brazilian nation.